Analytical procedure based on slurry sampling for determining selenium in organic vegetable samples by graphite furnace atomic absorption spectrometry - de Moraes, Paula Martin [UNESP]; Milantonio, Rafael Brunner [UNESP]; Cagnani, Gustavo Salustiano [UNESP]; dos Santos, Felipe Andre [UNESP]; Federici Padilha, Cilene do Carmo [UNESP]; de Lima, Paula Monteiro [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Springer, 2009)
This paper presents a simple, fast and sensitive method to determine selenium in vegetable samples by graphite furnace atomic absorption spectrometry through the direct introduction of slurries of the samples into the spectrometer's graphite tube. The limits of detection and quantification calculated for 20 readings of the blank of the standard slurries (5 mg mL(-1) of microcrystalline cellulose) were 0.33 and 1.10 mu g L(-1). The proposed method was applied to determine selenium in samples of organically grown vegetables and its results proved compatible with those obtained from samples mineralized by acid digestion in a microwave oven.
Keywords: Vegetable samples; Slurry sampling; Organic and convectional culture; Selenium determination; GFAAS